Perlindungan Hukum Youtuber Atas Publikasi Video yang Telah Dimonetisasi Pendistribusian Royalti oleh Lembaga Manajemen Kolektif - Vernando Samosir, Anju Doli; Christine S.T. Kansil (UNES Law Review, 2023)
The existence of regulations regarding Collective Management Institutions (LMK) in Law 28/2014 and the existence of monetization on YouTube should prevent YouTubers from copyright violations, because Article 87 of Law 28/2014 regulates that the use of works and/or is not considered a violation of Law 28/2014. Related Rights products commercially by users as long as the user has carried out and fulfilled the obligations in accordance with the agreement with LMK. However, there is one very interesting case to be studied in Decision 41PK/Pdt.Sus-HKI/2021 where the Defendant is the creator and owner of video content through the account/channel of YouTuber Gen Halilintar which has been monetized and has paid royalties to LMK, namely Wahana Musik Indonesia (WAMI) was sued by PT Nagaswara Publisherindo which is the copyright holder of a song creation (music and lyrics) entitled "Lagi Syantik" "Ciptaan". The purpose of writing this article is to find out and describe YouTubers' legal protection for video publications that have been monetized for distribution of royalties by LMK (Study Decision No. 41PK/Pdt.Sus-HKI/2021). The research method used is normative legal research. The results and conclusions show that legal protection is given to YouTubers who have monetized and paid royalties to their creators through LMK but must still pay attention to moral rights over the creation, namely by not making modifications to the creator's work.